Integration of corporate social responsibility into new product development - Chang-Lin Yang; Kai-Ping Huang; Ching-Lien Huang; Rong-Hwa Huang (International Journal of Management, Economics and Social Sciences (IJMESS), 2016)
This study investigated seven core subjects of ISO 26000 to explore the way in which new product development (NPD) links corporate social responsibility (CSR) strategy with product development planning. This study thoroughly discussed the implementation of policies that achieve social responsibility within the context of NPD planning. Rapid changes in science and technology mean customer needs are changing faster than ever before, making it increasingly difficult to identify critical customer needs in a timely manner. NPD therefore is essential to enhance enterprise competitiveness. The construction of a CSR-based NPD model can help enterprises in NPD. Using the CSR based NPD model to plan materials selection, specification setting, manufacturing procedures and methods, distribution, servicing and recycling increases enterprise friendliness and happiness, and benefits their sustainable development. The findings of this study suggest that traditional enterprise activities focus on profit maximization and cost minimization. The profit-oriented strategy influences product design, purchase, production, manufacture and delivery. Poor working environment, overtime, low wages, neglect of health and safety, and various deficiencies in CSR frequently occur. If a CSR based perspective is initially adopted to implement public expectations regarding product design, it can be both beneficial and environmentally friendly.
Keywords: L15; M11; M14; 330; New product development (NPD); corporate social responsibility (CSR); ISO 26000; sustainable development; competitive advantage